Unconsciousness in Patients with Suicidal Attempt History in Comparison with Others (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
One of the limitations in management of patients suffering from decreased level of consciousness due to drug poisoning is the inability to interview the patient. The aim of the present study was to compare characteristics of the two subgroups of these patients; those who had a suicidal attempt history with others. In this case-control study, 19 patients with suicidal attempt history and 66 patients without this history were selected among patients who were admitted for drug poisoning to Loghman hospital in Tehran, Iran, in April and May 2008. When they patients were admitted, all of them had decreased level of consciousness due to unknown drug poisoning. Demographic and poisoning characteristics, past medical history and substance use history of the patients were recorded.
Keywords: Psychological; history